Raziskovanje možnosti prilagoditve trenutnega načina gospodarjenja z mešanimi gorskimi gozdovi za povečanje vezave ogljika v gozdovih - Podvinšek, Suzana (Gozdarski vestnik, 2023)
Forests importantly mitigate the impact of climate change by ensuring CO2 sequestration and storing carbon (C). In our research, we focused on two ecosystem forest services: the production of timber as a basic raw material and carbon sequestration as an ecosystem service for mitigating (negative) impacts of climate change. We modelled forest development on two pilot areas, namely Pohorje and Dinaric Mountains. We performed the simulation using the SLOMATRIX population matrix model composed of four main modules, each simulating one of the key processes in uneven-aged forests: ingrowth, natural mortality, harvest (anthropogenic mortality), and growth of trees. In the framework of the project, we added a module for calculating the C sequestration. We simulated forest development for five tree species or tree species groups: fir, beech, spruce, other conifers, and broadleaves. We simulated the current forest management (BAU scenario), scenario without active management (NOM), and, using the linear programming, we looked for the COPT optimized scenario, at which we searched for the management scheme that would maximize C sequestration in forests in the next 100 years. In BAU and COPT scenarios, despite the minimal differences in the initial diameter structure of forests, we detected differences in the diameter structure and tree species composition of the harvested trees and two diverse approaches to C sequestration maximization. The first approach was characterized by a lower total number of harvested trees with a distinct emphasis on the harvest of fir; however, the harvested trees were on average of larger diameters than harvested trees in BAU. This approach was simulated in the Dinaric Mountains. In Pohorje a different approach was simulated; it was characterized by the harvest of a considerable share of thinner trees with an emphasis on spruce and beech, resulting in a substantial increase of large-diameter trees. We assume the differences in the optimization approaches may be caused by diverse site productivities and differences in the proportions of slow, medium-fast, and fast-growing trees.
Keywords: carbon sequestration; forest management scenarios; lesnoproizvodna funkcija; modeliranje razvoja gozdov; modelling forest development; scenariji gospodarjenja z gozdovi; sekvestracija ogljika; timber production function